Fecal alpha-1 antitrypsin concentration in protein-losing enteropathies caused by Rotavirus and enteropathogenic bacteria infection - D. Aulia; I. S. Timan; A. Firmansyah (Indonesian Pediatric Society, 2009)
Background An increase in protein loss through the intestinallumen is commonly found in children with intestinal inflammation. Measurement of fecal alpha-1 antitrypsin (FAA T) concentration has been used to detect the loss of protein through the digestive system. FAAT concentration increases in diarrhea patients due to Rotavirus, Adenovirus, Shigella, Enterotoxigenic E. coli (ETEC), and Salmonella infection.Objective To determine the relationship between types ofpathogen, acute diarrhea, and alpha-1 antitrypsin concentrationin children with acute diarrhea caused by Rotavirus andenteropathogenic infection.Methods Descriptive statistics and proportion difference betweenthe two non-related groups were used to assess the proportion ofprotein-losing enteropathy (PLE) in children with acute diarrheaand was analyzed using chi square test.Results In this study, PLE group comprised 25% (24/95) subjectswithout unknown cause of diarrhea, 50% (4 7 /95) had one typeof pathogen, and in 23% (22/95) subjects had 2 or more types of pathogens. The most common pathogen found in PLE group was Rotavirus, found in67 (53%) subjects and E. coli in 41 (33%) subjects. In non-PLE group, we also found similar pathogen pattern. The mean alpha-1 antitrypsin (AAT) concentration in acute diarrhea group due to Rotavirus infection was significantly higher (P= 0.003) compared to acute diarrhea groups caused by non-Rotavirus infection. The mean AAT concentration in acute diarrhea group due to E. coli infection did not differ significantly (P= 0.735) compared to acute diarrhea group caused by non-E. coli infection.Conclusion Rotavirus was a more significant cause of PLEcompared to E.coli.